Managing supplier relations with balanced scorecard. (28th January 2008) - Brege, Staffan; Brehmer, Per-Olof; Rehme, Jakob
As a consequence of increased outsourcing, companies become more and more virtual organisations and dependent upon external sources to reach their strategic objectives. Here, lacking supplier performance or commitment can result in failure of the outsourcing programme that significantly risks the financial results of the outsourcing company. Consequently, when outsourcing it is important to assure that the supplier performs as expected. This study uses a Balanced Scorecard (BSC) perspective for investigating performance measurements in outsourcing. The results illustrate the importance of a process perspective when outsourcing (securing volume, high quality at the right time). Formulating a BSC for a supplier, an outsourcing company could better control/steer the supplier on an output/performance level.